Radiological imaging of the wrist joint. Issue 4 (August 2017) - Heire, Priam; Temperley, David; Murali, Raj
Abstract: The anatomy and biomechanics of the wrist are complex and the joint can be affected by a wide range of pathology. Here, we explain the radiological anatomy of the wrist joint with respect to various imaging modalities. Trauma is a major cause of wrist pain and disability and can involve fractures, ligamentous and other soft tissue injuries. Fractures of the scaphoid can lead to avascular necrosis, non-union and accelerated osteoarthritis. Injuries of the intrinsic ligaments can disrupt the normal biomechanical relationship of the scaphoid and trapezium and cause instability and scapholunate advanced collapse. Carpal dislocations are severe injuries and include lunate dislocation, where the lunate dislocates in a volar direction, or perilunate dislocation, where there is dislocation of the carpus relative to the lunate. Tears of the triangular fibrocartilage can be traumatic or degenerate and best imaged with MR arthrography. Diagnosis of distal radioulnar joint instability can be problematic but there are various methods which can be employed, including the Mino, epicentre and congruency techniques. The wrist joint can be involved in all types of arthropathy, most commonly osteoarthritis which is commonly seen at the base of the thumb. Rheumatoid arthritis is an inflammatory condition and ultrasound is a very sensitive examination for assessment of active synovitis, tenosynovitis or tendon rupture.